Oncolytic viruses: a potential breakthrough immunotherapy for multiple myeloma patients - Raimondi, Vincenzo; Vescovini, Rosanna; Dessena, Mattia; Donofrio, Gaetano; Storti, Paola; Giuliani, Nicola (Frontiers in Immunology, 2024)
Oncolytic virotherapy represents an innovative and promising approach for the treatment of cancer, including multiple myeloma (MM), a currently incurable plasma cell (PC) neoplasm. Despite the advances that new therapies, particularly immunotherapy, have been made, relapses still occur in MM patients, highlighting the medical need for new treatment options.Oncolytic viruses (OVs) preferentially infect and destroy cancer cells, exerting a direct and/or indirect cytopathic effect, combined with a modulation of the tumor microenvironment leading to an activation of the immune system. Both naturally occurring and genetically modified viruses have demonstrated significant preclinical effects against MM cells. Currently, the OVs genetically modified measles virus strains, reovirus, and vesicular stomatitis virus are employed in clinical trials for MM. Nevertheless, significant challenges remain, including the efficiency of the virus delivery to the tumor, overcoming antiviral immune responses, and the specificity of the virus for MM cells. Different strategies are being explored to optimize OV therapy, including combining it with standard treatments and targeted therapies to enhance efficacy. This review will provide a comprehensive analysis of the mechanism of action of the different OVs, and preclinical and clinical evidence, focusing on the role of oncolytic virotherapy as a new possible immunotherapeutic approach also in combination with the current therapeutic armamentarium and underlying the future directions in the context of MM treatments.